Non-1st seizure was less severe than 1st seizure with non-urgent level among suspected seizures transferred by ambulance. - Yotaro Asano; Ayataka Fujimoto; Keisuke Hatano; Keishiro Sato; Takahiro Atsumi; Hideo Enoki; Tohru Okanishi (PLoS ONE, 2023)
Background To prioritize emergency medical calls for ambulance transport for patients with suspected seizures, information about whether the event is their 1st or non-1st seizure is important. However, little is known about the difference between 1st and non-1st seizures in terms of severity. We hypothesized that patients transferred multiple times (≥2 times) would represent a milder scenario than patients on their first transfer. The purpose of this study was to compare patients with suspected seizures on 1st transfer by ambulance and patients who had been transferred ≥2 times. Methods We statistically compared severity of suspected seizures between two groups of patients with suspected seizures transferred between December 2014 and November 2019 (before the coronavirus disease 2019 pandemic) to our facility by ambulance for either the first time (1st Group) or at least the second time (Non-1st Group). Severity categories were defined as: Level 1 = life-threatening; Level 2 = emergent, needing admission to the intensive care unit; Level 3 = urgent, needing admission to a hospital general ward; Level 4 = less urgent, needing intervention but not hospitalization; and Level 5 = non-urgent, not needing intervention. Results Among 5996 patients with suspected seizures conveyed to the emergency department by ambulance a total of 14,263 times during the study period, 1222 times (8.6%) and 636 patients (11%) met the criteria. Severity grade of suspected seizures ranged from 1 to 5 (median, 4; interquartile range, 3-4) for the 1st Group and from 1 to 5 (median, 5; interquartile range, 4-5) for the Non-1st Group. Most severe grade ranged from 1 to 5 (median, 4; interquartile range, 4-5) for the Non-1st Group. Severity grade differed significantly between groups (p < 0.001, Mann-Whitney U-test). Uni- and multivariate logistic regression tests also suggested a significant difference (p < 0.001) in severity grades. Conclusion In direct comparisons, grade of suspected seizure severity was lower in the Non-1st Group than in the 1st Group.